Membangun Sinergi antara Civitas Akademik dengan Aparatur Desa Kampung Jongok Bathin dalam Mempersiapkan Generasi Muda menghadapi Era Digital 5.0 - Syafridha Yanti; Murthada; Sulistio Ningsih (LSM Catimore dan Sahabat, 2023)
This Community Service Program is a collaborative service program carried out by several Study Programs, including Economic Education Study Program, PPKN Study Program, English Language Education Study Program, and Physical Education. which carries the theme of building Synergy Between the Academic Community and Kampung Jongok Bathin Village Apparatuses in Preparing the Young Generation to Face the Digital Era 5.0, in collaboration with Kampung Jongok Bathin Village apparatus. In this Community Service Program, the material for preparing young people to face the Digital 5.0 era is expected to be able to provide education to the people of Kampung Jongok Bathin about the meaning, types, dangers, how to protect and manage them. It is also hoped that through this material the public / Internet users will know what personal information can be left on the internet when surfing the web and using social media. And users also need to know that personal information that is left scattered on the internet can make them open to all kinds of threats, from identity theft to physical harassment. The purpose of the presentation of the material in this Collaborative Program between Study Programs is to educate so that people can be smarter and users are asked to be wise in interacting on the internet. The community or internet users must be equipped with knowledge to realize that all activities on the internet are recorded and the data is spread to various parties. For this reason, it is very important for users to take various preventive measures, especially related to data privacy and security. The method of implementing this service program is carried out in several stages of implementation as follows: Compiling service protocols, initial survey of locations and target issues, meetings with the Village Head and Village officials, Dissemination of the material presented. In the presentation of counseling material using the lecture method and using power point slide media. The conclusion of this community service is that with the socialization and training that is delivered, it can increase the knowledge and understanding of the community, especially digital footprints (Digital footprint) and the community can be more self-aware in exploring the internet.